Pengaruh Small Side Game melalui Interval, Pyramid dan Mix Method Training terhadap Peningkatan Speed 30m Pemain Sepakbola - Janviera, Egi Dinda; Imanudin, Iman; Hardwis, Syam; Fadli, Muhamad (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the effect of training with interval, pyramid, and mix methods in small sided game (SSG) on increasing 30-meter speed. This study uses a quantitative design with a pre-test and post-test approach to compare the three training methods. The research sample consisted of 30 male soccer athletes aged 17 to 18 years from the Persib Bandung Academy who followed a 6-week training program. Sampling was carried out using a simple random sampling technique. The data collected were analyzed using parametric statistics, after passing the normality, homogeneity, and paired sample t-test tests by showing results that met the requirements. The results showed that there was no significant difference between the interval, pyramid, and mix training groups in increasing 30-meter running speed.